2017
DOI: 10.1080/01635581.2017.1340491
|View full text |Cite
|
Sign up to set email alerts
|

Black Raspberries and Their Anthocyanin and Fiber Fractions Alter the Composition and Diversity of Gut Microbiota in F-344 Rats

Abstract: Natural compounds can alter the diversity and composition of the gut microbiome, potentially benefiting our health. We previously demonstrated chemopreventive effects of black raspberries (BRBs) in colorectal cancer, which associates with gut dysbiosis. To investigate the effects of whole BRBs and their fractions on gut microbiota, we fed F-344 rats a control diet, 5% BRBs, the BRB anthocyanin fraction, or the BRB residue fraction for 6 weeks. Feces were collected at baseline and at weeks 3 and 6, and bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 48 publications
(56 reference statements)
3
62
0
1
Order By: Relevance
“…Gut microbiota breaking of glycosidic linkages and breakdown of anthocyanidin heterocycle are both meditated via bacterial enzymatic activity. This way, anthocyanins are transformed into their more bioavailable forms that, in turn, may regulate the colonic microbiota composition (Figure 2) [61,76,81,84].…”
Section: Ratmentioning
confidence: 99%
“…Gut microbiota breaking of glycosidic linkages and breakdown of anthocyanidin heterocycle are both meditated via bacterial enzymatic activity. This way, anthocyanins are transformed into their more bioavailable forms that, in turn, may regulate the colonic microbiota composition (Figure 2) [61,76,81,84].…”
Section: Ratmentioning
confidence: 99%
“…Inulins have been reported to stimulate growth or activity pf beneficial bacteria and suppress the level of harmful bacteria selectively [ 55 , 56 ]. Recent studies also showed that anthocyanins from blackberries could alter the composition and diversity of microbiota [ 57 ]. In the PB pretreatment group, the composition of the microbiota was more similar to health controls which suggest that the PB could help maintain the homeostasis of gut flora.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, many new sequences have been isolated from human and animal intestine that can be identified as the genus Barnesiella . Nevertheless, it still remains unclear how the abundance of Barnesiella is linked to inflammatory diseases of the gastrointestinal tract [ 57 ]. Some reports shed light on the function of Barnesiella, reporting that Barnesiella bacteria contribute to the elimination and protection against vancomycin-resistant Enterococcus faecium colonization [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, healthy mice fed with 20% apple flesh/peel for 7 or 21 days showed increased number of beneficial Bifidobacterium and decreased expression of inflammatory genes in jejunum tissue including IL‐2 receptor b (IL2rb), chemokine receptor‐2 (ccr2), ccr10, and decreased plasma prostaglandin E 2 (PGE 2 ) and TNF‐α levels compared to control mice . Moreover, 5% black raspberries increased the abundance of Akkermansia and Desulfovibrio microbial species, which possess anti‐inflammatory effects and increased the Anaerostipes , butyrate‐(SCFA)‐producing bacteria, in F‐344 rats after 6 weeks of treatment . Mice fed with 300 mg per kg body weight per day pro‐anthocyanidin extract from grapes for 7 weeks modulated Clostridium , Roseburia , and Prevotella composition and decreased the epididymal fat mass .…”
Section: Impact Of Gut Microbiota On Obesity and Inflammationmentioning
confidence: 98%